Pyrrole- and indole-containing tranylcypromine derivatives as novel lysine-specific demethylase 1 inhibitors active on cancer cells1. Issue 4 (10th April 2015) - Rodriguez, Veronica; Valente, Sergio; Rovida, Stefano; Rotili, Dante; Stazi, Giulia; Lucidi, Alessia; Ciossani, Giuseppe; Mattevi, Andrea; Botrugno, Oronza A.; Dessanti, Paola; Mercurio, Ciro; Vianello, Paola; et al.
<x xml:space="preserve">Abstract</x> A new series of pyrrole/indole-containing tranylcypromine analogues is reported as potent and selective LSD1 inhibitors active in leukemia.